Ecological Characteristics of a Gonystylus bancanus-rich Area in Pekan Forest Reserve, Pahang, Malaysia - Khali Aziz Hamzah; Ismail Parlan; Abd Rahman Kassim; Che Hashim Hassan; Grippin Akeng; Nizam Mohd Said (Tropical Life Sciences Research, 2009)
Tropical peat swamp forest (PSF) is a unique wetland ecosystem with distinct vegetation types. Due to the waterlogged environment, the stand characteristics in this ecosystem are different from those of other inland forests. This paper highlights stand characteristics of a PSF based on our investigation of a 1 ha ecological plot established in a Virgin Jungle Reserve (VJR) at Compartment 100, Pekan Forest Reserve, Pahang, Malaysia. This site is considered a Gonystylus bancanus-rich area. From the inventory, we recorded a total of 49 tree species from 38 genera and 25 families among all trees of ? 10 cm in diameter at breast height. Calophyllum ferrugineum var. ferrugineum was the most abundant species, followed by G. bancanus. The forest appeared healthy, as all tree characteristics (crown shape, log grade and climber infestation) generally fell within Classes 1 and 2 (good and moderate categories), with the exception of crown illumination which majority of the trees were rated as class 3 (received less sunlight). The latter finding indicates that most of the trees living under the canopy received minimal illumination. In terms of total tree biomass, we estimated that about 414.6 tonnes exist in this 1 ha area; this tree biomass is higher than in some PSF areas of Sumatra, Indonesia. Hutan paya gambut (HPG) tropika merupakan satu ekosistem tanah lembap yang unik dengan pelbagai jenis tumbuhan. Oleh kerana secara umum persekitarannya merupakan air yang bertakung menyebabkan sifat-sifat dirian di sini berbeza dari dirian hutan darat yang lain. Kertas kerja ini menerangkan ciri-ciri dirian HPG berdasarkan kajian di petak 1 ha yang ditubuhkan di kawasan Hutan Simpanan Hutan Dara di Kompatmen 100, Hutan Simpan Pekan, Pahang, Malaysia. Kawasan ini dikategorikan sebagai kaya dengan spesies Gonystylus bancanus. Hasil dari inventori, kami merekodkan sejumlah 49 spesies dari 38 genera dan 25 famili bagi semua pokok >10 cm pada perepang paras dada. Calophyllum ferrugineum var. ferrugineum merupakan spesies paling dominan diikuti oleh G. bancanus. Kawasan hutan berkenaan boleh dikatakan sebagai sihat memandangkan semua ciri pokok (bentuk silara, gred balak dan gangguan pepanjat) secara umumnya pada Kelas 1 dan 2 (baik dan sederhana), kecuali pencahayaan silara yang mana majoriti pokok adalah pada Kelas 3 (terima kurang cahaya). Keadaan tersebut menunjukkan kebanyakan pokok di bawah naungan menerima cahaya matahari yang minimal. Dari segi biomass pokok, kami menganggarkan sebanyak 414.6 ton di dalam petak 1 ha ini yang menunjukkan biomass pokok di sini adalah lebih tinggi berbanding dengan beberapa kawasan HPG di Sumatra, Indonesia.